Vegetative and Engineering Measures for Torrent Training and Stream Bank Protection in the Doon Valley - Singh, Bakhshish; Mathur, H. N.; Gupta, S. K. (Indian Forester, 1971)
Lot of areas are lying waste and are threatened with stream bank erosion in the Sub-Himalayan region. A study was, therefore, undertaken at the Soil Conservation Research Station, Dehra Dun in the Bainkhala torrent to See the performance of vegetative measures and engineering structures, singly or in combination with each other, for channelisation of the torrent with the object to reclaim excels areas under the bed for proper land utilisation and also to check bank cutting. The principle of torrent training and details of the various structures tried are given in this paper. Moreover, their functioning and performance have also been reported; and based upon the experience gained from these trials for about 10 years from 1958 to 1967, the authors have recommended a rational scheme for torrent control works in this region.